Enhanced Uptake and Phototoxicity of C60@albumin Hybrids by Folate Bioconjugation - Andrea Cantelli; Marco Malferrari; Edoardo Jun Mattioli; Alessia Marconi; Giulia Mirra; Alice Soldà; Tainah Dorina Marforio; Francesco Zerbetto; Stefania Rapino; Matteo Di Giosia; Matteo Calvaresi (Nanomaterials, 2022)
Fullerenes are considered excellent photosensitizers, being highly suitable for photodynamic therapy (PDT). A lack of water solubility and low biocompatibility are, in many instances, still hampering the full exploitation of their potential in nanomedicine. Here, we used human serum albumin (HSA) to disperse fullerenes by binding up to five fullerene cages inside the hydrophobic cavities. Albumin was bioconjugated with folic acid to specifically address the folate receptors that are usually overexpressed in several solid tumors. Concurrently, tetramethylrhodamine isothiocyanate, TRITC, a tag for imaging, was conjugated to C60@HSA in order to build an effective phototheranostic platform. The in vitro experiments demonstrated that: (i) HSA disperses C60 molecules in a physiological environment, (ii) HSA, upon C60 binding, maintains its biological identity and biocompatibility, (iii) the C60@HSA complex shows a significant visible-light-induced production of reactive oxygen species, and (iv) folate bioconjugation improves both the internalization and the PDT-induced phototoxicity of the C60@HSA complex in HeLa cells.